Plasma Leak From the Circulation Contributes to Poor Outcomes for Preterm Infants: A Working Hypothesis - Eiby, Yvonne A.; Lingwood, Barbara E.; Wright, Ian M. R. (Frontiers in Neurology, 2021)
Preterm infants are at high risk of death and disability resulting from brain injury. Impaired cardiovascular function leading to poor cerebral oxygenation is a significant contributor to these adverse outcomes, but current therapeutic approaches have failed to improve outcome. We have re-examined existing evidence regarding hypovolemia and have concluded that in the preterm infant loss of plasma from the circulation results in hypovolemia; and that this is a significant driver of cardiovascular instability and thus poor cerebral oxygenation. High capillary permeability, altered hydrostatic and oncotic pressure gradients, and reduced lymphatic return all combine to increase net loss of plasma from the circulation at the capillary. Evidence is presented that early hypovolemia occurs in preterm infants, and that capillary permeability and pressure gradients all change in a way that promotes rapid plasma loss at the capillary. Impaired lymph flow, inflammation and some current treatment strategies may further exacerbate this plasma loss. A framework for testing this hypothesis is presented. Understanding these mechanisms opens the way to novel treatment strategies to support cardiovascular function and cerebral oxygenation, to replace current therapies, which have been shown not to change outcomes.